Factors Affecting The Quality of Regional Financial Statements of Luwu Regency - Safitri, Alya; Caronge, Erniyati; Sultan, Sultan (Journal of Applied Business, Taxation and Economics Research, 2026)
This study aims to analyze the influence of understanding of Government Accounting Standards (SAP), the use of the Regional Financial Accounting Information System (SIAKD), internal control systems, and human resource competencies on the quality of regional financial statements. This study uses a quantitative approach with a type of causal associative research. The research was carried out at the Regional Finance and Assets Agency (BKAD) of Luwu Regency. The research population was all employees of BKAD Luwu Regency totaling 43 people, which were also used as samples with saturated sampling techniques. The data used were primary data obtained through a questionnaire with a five-point Likert scale. Data analysis was carried out using descriptive statistics, validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis through t-tests, F tests, and determination coefficients. The results of the study show that the understanding of SAP, the use of SIAKD, the internal control system, and the competence of human resources have a positive and significant effect on the quality of regional financial statements. The implications of this study show the importance of improving human resource competence, strengthening SAP understanding, optimizing SIAKD, and strengthening the internal control system to improve the quality of regional financial reports.